The effect of preliminary oxidized carbon support on the activity of copper supported catalysts of ethanol dehydrogenation - Е. А. Ponomareva; Е. V. Egorova; A. S. Parastaev; D. А. Bokarev; E. G. Cheblakova; I. A. Malinina (Тонкие химические технологии, 2014)
Copper supported catalysts based on preliminary oxidized carbon fibers have been studied. Nitric acid and hydrogen peroxide have been used for prior oxidation treatment of the supports. To characterize this materials N2 adsorption-desorption and titration technics were used. Compared to nonoxidized activated carbon fibers, no significant changes in the texture of the modified supports were found, while there were differences in surface functionalities. Cupper supported catalysts were prepared by wetness impregnation and characterized by TPR, SEM. The influence of different surface functional groups on the distribution of active metal has been discussed. Besides, the catalysts were tested in the process of ethanol dehydrogenation. Cupper supported on activated carbon fibers preliminary oxidized with HNO3 appeared to be more active in the process, although less stable at high temperatures. The reasons of the loss of activity have been also discussed.